Study of the regularities of centerline porosity formation in continuously cast billets depending on casting parameters - Synehin, Yevhen; Ruban, Volodymyr; Niziaiev, Kostiantyn; Stoianov, Oleksandr; Zhuravlova, Svitlana (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process that forms centerline porosity in the axial zone of a continuously cast steel billet during its hardening. The task addressed relates to the need to establish rational parameters for the temperature-speed mode of casting to minimize axial porosity, which is critical for increasing the density of the metal and the quality of rolled products. A comprehensive methodology for physical modeling of the hardening process using stearin as a model substance has been devised. Based on the analysis of similarity numbers (Biot, Fourier, Kosovych), the exact scales of modeling were established: by time – 1.854, by linear dimensions – 0.1778, by heat transfer coefficient – 0.04639. It was determined that for an adequate simulation of the formation of the bloom blank, the closing angle of the liquid core varies within 2.3–6°. Quantitative parameters of the experiment on the model were established: overheating of the melt in the range of 1.8–4.2°C, which corresponds to 15–35°C for steel. The resulting data are explained by the laws of convection heat transfer and phase transition. The angle of inclination of the crystallization front and the intensity of heat removal determine the moment of formation of "bridges" and interceptions in the thermal center, which directly defines the morphology and volume of shrinkage pores. Unlike conventional mathematical modeling, the proposed approach provides high visual reliability of defect formation due to the use of the π-theorem for the selection of physical parameters. This makes it possible to investigate critical system states without the risk of emergencies in industrial settings. The research results could be used for implementation at metallurgical enterprises in the design and optimization of billet cooling modes on a continuous billet casting machine (CCM), which will ensure an increase in the yield of suitable metal